Sheep Acclimation in the Andean highlands - Report related to artificial insemination experimental campaign conducted in the highlands of the center during the months of May and June 1944 - Atkins M., J. (1945)
It was inseminate the largest number of sheep on different farms, in order to check to what extent it was possible in practice to use artificial insemination for improvement of sheep farms in the highlands of the Sierra Center.